Implementasi Layanan Bimbingan Dan Konseling Di SMPN 2 Karawang - Neneng Soliha H; Rahma Faudziah; Ramaditya Saleh; Ribby Fadilla A; Nur Aini Farida (CV. SINAR HOWUHOWU, 2025)
This study aims to describe the implementation of Guidance and Counseling (BK) services at SMPN 2 Karawang Barat and identify the roles, challenges, and expectations of students and teachers regarding these services. Data were obtained through observation, interviews with guidance and counseling teachers, subject teachers, students, and documentation studies. The results indicate that guidance and counseling services at SMPN 2 Karawang Barat have been implemented quite well, with various forms of service, such as individual counseling, group counseling, information services, and classroom services. The main focus of this year's program is academic mentoring, discipline coaching, and the development of student talents and interests. Collaboration between stakeholders, including homeroom teachers, subject teachers, Islamic Religious Education teachers, the principal, and parents, is a crucial supporting factor, although it is not yet implemented systematically. Students perceive BK as a safe place to share their experiences and find solutions, although some still prefer to share their problems with close friends. The main challenges faced are low parental involvement and the stigma that BK is only for students with problems. Analysis of the theory indicates that the alleviation function is more dominant than the prevention and development functions. Thus, the guidance and counseling services at SMPN 2 West Karawang are considered quite effective in addressing student issues. However, they still need to be strengthened in terms of prevention, potential development, and more structured collaboration.